Question
upstudy study bank question image url

Using the method of substitution, fill in the bla The solution set of the system \( \left\{\begin{array}{l}x-y-z=4 \\ x+y-z=12 \\ x-y+z=-4\end{array}\right. \)

Ask by Pierce King. in Iraq
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution to the system is \( x = 4 \), \( y = 4 \), and \( z = -4 \).

Solution

We are given the system:   (1) x – y – z = 4   (2) x + y – z = 12   (3) x – y + z = –4 Step 1. Solve equation (1) for x:   x = 4 + y + z Step 2. Substitute x = 4 + y + z into equation (2):   (4 + y + z) + y – z = 12   4 + 2y = 12 Subtract 4 from both sides:   2y = 8, so  y = 4 Step 3. Now substitute y = 4 into the expression for x:   x = 4 + 4 + z ⇒ x = 8 + z Step 4. Substitute x = 8 + z and y = 4 into equation (3):   (8 + z) – 4 + z = –4   8 + z – 4 + z = –4   4 + 2z = –4 Subtract 4 from both sides:   2z = –8, so  z = –4 Step 5. Now find x:   x = 8 + z = 8 + (–4) = 4 Thus, the solution set is:   x = 4, y = 4, z = –4 So, the unique solution to the system is (4, 4, –4).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the system using substitution, let's start with one of the equations and express one variable in terms of the others. For simplicity, we can take the first equation \(x - y - z = 4\) and isolate \(x\): \[ x = y + z + 4 \] Now, we can substitute this expression for \(x\) into the other two equations. Substituting into the second equation \(x + y - z = 12\): \[ (y + z + 4) + y - z = 12 \] Simplifying this gives: \[ 2y + 4 = 12 \] \[ 2y = 8 \] \[ y = 4 \] Now that we have \(y\), we can substitute \(y = 4\) back into the expression for \(x\): \[ x = 4 + z + 4 \] So, \[ x = z + 8 \] Next, substitute \(y = 4\) into the first equation to find \(z\): \[ x - 4 - z = 4 \] Substituting \(x = z + 8\): \[ (z + 8) - 4 - z = 4 \] This simplifies to: \[ 4 = 4 \] This means we have found the relationship between \(x\), \(y\), and \(z\) but not specific values for \(z\). Hence, we can express \(x\) in terms of \(z\): Now let’s use the third equation \(x - y + z = -4\): Substituting \(y = 4\) and \(x = z + 8\): \[ (z + 8) - 4 + z = -4 \] This leads to: \[ 2z + 4 = -4 \] Simplifying gives: \[ 2z = -8 \] So, \[ z = -4 \] Now we can find \(x\) using \(z = -4\): \[ x = -4 + 8 = 4 \] We already found \(y = 4\). The solution set of the system is: \[ (x, y, z) = (4, 4, -4) \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy